Análisis sobre la constitucionalidad de la facultad de la DIAN para seleccionar destinatarios de la acción penal - Gutiérrez Piña, Jennifer Carolina (Universidad Antonio Nariño, 2023)
The Colombian legal system establishes three tax behaviors classified as crimes in the Colombian criminal code, which are: tax fraud or evasion, Omission of assets or declaration of these for a lower value or inclusion of non-existent liabilities in the income statement and Omission of the withholding agent or collector